2018
DOI: 10.3390/genes9110544
|View full text |Cite
|
Sign up to set email alerts
|

Population Connectivity and Traces of Mitochondrial Introgression in New Zealand Black-Billed Gulls (Larus bulleri)

Abstract: Black-billed gulls (Larus bulleri) are endemic to New Zealand and are suspected to be undergoing substantial population declines. They primarily breed on open gravel beds in braided rivers of the South Island—a habitat that is diminishing and becoming increasingly modified. Although management of this species is increasing, little has been published on their movements and demographics. In this study, both mitochondrial DNA (mtDNA) control region domain I and nuclear single nucleotide polymorphisms (SNPs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…The results from this population indicated that these samples had a high frequency of mtDNA haplotypes from Red-billed Gulls (six out of 26 samples, 23%). A recent study (Mischler et al 2018) collected 69 blood samples from 10 Black-billed Gull colonies in different parts of New Zealand. The study found that, overall, 16% showed mtDNA introgression.…”
Section: Why Does Hybridization Occur Among Masked Gulls?mentioning
confidence: 99%
See 2 more Smart Citations
“…The results from this population indicated that these samples had a high frequency of mtDNA haplotypes from Red-billed Gulls (six out of 26 samples, 23%). A recent study (Mischler et al 2018) collected 69 blood samples from 10 Black-billed Gull colonies in different parts of New Zealand. The study found that, overall, 16% showed mtDNA introgression.…”
Section: Why Does Hybridization Occur Among Masked Gulls?mentioning
confidence: 99%
“…The first documented account of interbreeding of the two New Zealand species of masked gulls was between five pairings of Red-billed Gulls Chroicocephalus novaehollandiae scopulinus and Black-billed Gulls Chroicocephalus bulleri at Lake Rotorua (Gurr 1967). More recently, mtDNA analysis of 69 adult Black-billed Gulls collected at 10 colonies at different localities revealed the presence of mtDNA haplotypes characteristic of Redbilled Gulls (Mischler et al 2018). This pattern can be explained by hybridization between the two species, though incomplete lineage sorting could not be excluded as an alternative mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial DNA (mtDNA) differs from nuclear data in that it represents a short (15-20,000 base pairs (bp)), circular sequence of DNA (the mitogenome) that is maternally inherited, and found as 10-1000s of copies present in most cells of an individual (O'Hara et al, 2019). These properties make mtDNA useful independently or in combination with nuclear genetic markers for broad-scale comparisons of population-level diversity and differentiation (Alexander et al, 2016;Chapple et al, 2012;Mischler et al, 2018), taxonomic delimitation and phylogenetic inferences (Banker et al, 2017;Boon et al, 2000;Rosenbaum et al, 2017), and for investigating potential drivers of extinction, including in ancient DNA analysis (Allentoft et al, 2014…”
Section: Mitochondrial Datamentioning
confidence: 99%
“…In other cases, broader phylogenetic understanding of a group can directly inform different kinds of conservation practice and measures [4,9]. Expanded analyses of historical and ancient DNA now afford novel opportunities for better understanding relevant processes, including contemporary and past hybridization [10][11][12]. In addition, metagenomics and environmental (e)DNA allow for broader access to genetically sample ecosystems in new and rapid ways [13][14][15].…”
mentioning
confidence: 99%